Academic Administrators' Performance: Proposed Enhancement Activities - Cadosales, Maria Nancy Q. (JPAIR Multidisciplinary Research, 2009)
The purpose of this study was to evaluate the academic administrators' performance at La Salle University, Ozamiz City as rated by the teachers for the first semester of the academic year 2006-2007. Based on the findings of the study, enhancement activities were designed. The study employed the descriptive research to evaluate the academic administrators' performance. These academic administrators were the coordinators, program heads and college deans. It gathered data from the analysis of the academic administrators' performance rating to evaluate their competencies in management and administration; and professional and public service. Included in the year-end evaluation, are the personal qualities and interpersonal relationship skills of the academic administrators. Results reveal that academic administrators are performing multiple duties. They perform well in some areas as shown in the very satisfactory ratings. There are areas that the academic administrators had low ratings. Thus, there is a need to evaluate them regularly in order to identify the areas that they need further training.
Keywords: Academic administrators; performance; enhancement activities